Penurunan Kadar Kolesterol Pada Kuning Telur Asin dengan Perendaman Seduhan Serbuk dan Ekstrak Daun Salam (Syzygium Polyanthum) dengan Variasi Lama Perendaman - Kiky Candrawati; Nur Hidayati (Biomedika, 2019)
Egg has a good nutrient, but egg yolk also has high cholesterol so if we eat it excessive, it will do serious damage in our body and increasing the risk of coronary heart disease. Therefore, needed an inovation in food processing industry to process healthier foods and low cholesterol. One of the way by decreasing cholesterol levels in egg yolk by bay leaf (Syzygium polyanthum). Extract and powder of bay leaf (Syzygium polyanthum) were made to decreasing cholesterol levelsin egg yolk. After that, extract and powder solution of bay leaf were made with 2% of consentration. Uncooked eggswere soaking at extract and powder solution for 12 and 24 hours. Then, uncooked eggs were steam and do cholesterol examination with “CHOD-PAP” method and also do organoleptictesting involving 30 panelist. The result showed that soaking with extract of bay leaf for 24 hoursshowed higher decreasing cholesterol levelswhich has measured of 231 mg/100g. Cholesterol levels of egg before soaking knowing which has measured of 621 mg/100g, so that the percentage of decline is 62,80%. Statistic analysis with two ways ANOVA showed that there is a significant different in cholesterol levels. Organoleptic testinghas showed if consumen like the egg.